Temporal Changes in Erectile Function and Endothelium-Dependent Relaxing Response of Corpus Cavernosal Smooth Muscle After Ischemia by Ligation of Bilateral Internal Iliac Arteries in the Rabbit - Yuko Abe; Yuji Hotta; Kana Okumura; Tomoya Kataoka; Yasuhiro Maeda; Kazunori Kimura (Elsevier, 2012)
We aimed to elucidate the changes in the relaxation function of corpus cavernosal smooth muscle (CCSM) and erectile function using acute penile ischemic rabbits. Relaxation response to acetylcholine (Ach) was unchanged at 3 days after ischemia. The response to ACh had significantly decreased at 1 week, but had recovered completely at 4 weeks. The reaction to sodium nitroprusside and electrical field stimulation was unchanged by ischemia at all time points. Erectile function was changed in the same manner as the response of ACh. The endothelium-dependent relaxing responses of CCSM and erectile function were found to be initially decreased, but subsequently improved completely. Keywords:: arteriogenic erectile dysfunction, corpus cavernosal smooth muscle, endothelium